Optimization of spray drying parameters for pink guava powder using RSM - Shishir, Mohammad Rezaul Islam; Taip, Farah Saleena; Ab. Aziz, Norashikin; A. Talib, Rosnita; Sarker, Md. Sazzat Hossain (Korean Society of Food Science and Technology, 2016)
The optimization of pink guava was executed using central composite face-centred design to optimize the spray drying parameters of inlet temperature, maltodextrin concentration (MDC) and feed flow (FF). The experimental results were significantly (p<0.01) fitted into second-order polynomial models to describe and predict the response quality in terms of the final moisture, particle size and lycopene with R2 of 0.9749, 0.9616, and 0.9505, respectively. The final moisture content significantly (p<0.01) decreased with increasing inlet temperature and MDC, whereas the particle size increased. In contrast, the lycopene content significantly (p<0.01) decreased with the higher temperature and increased with increasing MDC. However, according to multiple response optimization, the optimum conditions of 150°C inlet temperature, 17.12% (w/v) MDC and 350 mL/h FF-predicted 3.10% moisture content, 11.23 μm particle size and 58.71 mg/100 g lycopene content. The experimental observation satisfied the predicted model within the acceptable range of the responses.